The Prevalence of Malnutrition and Sarcopenia and the Relationship with Inflammation and Anemia Among Community-Dwelling Older Adults: A Preliminary Cross-Sectional Study - Kornanong Yuenyongchaiwat; Chareeporn Akekawatchai; Khaimuk Changsri (Geriatrics)
Background: Older people are more likely to have poor nutrition and low muscle mass, which leads to poor physical performance and anemia, resulting in a poor quality of life and risks to mobility and mortality. Furthermore, malnutrition may, in part, raise the level of inflammatory biomarkers as well as muscle catabolism. Moreover, a range of indices related to systemic inflammation, obtained from routine complete blood count (CBC) tests, have been applied to inflammation markers. However, these biomarkers remain insufficiently addressed in the evidence supporting the presence of sarcopenia and malnutrition. This study aimed to explore sarcopenia in terms of malnutrition, anemia, and inflammation among Thai community-dwelling older people. Methods: This study enrolled community-dwelling older people aged 60 years and above. All participants were requested to complete a questionnaire assessing for sarcopenia (SARC-F) and nutritional status using the mini nutritional assessment (MNA). In addition, blood samples were obtained for the CBC test. Logistic regression analysis explored the risk of sarcopenia, CBC, and malnutrition status. Results: Of 126 older people (aged 62–88 years) enrolled, 12 individuals (9.52%) had sarcopenia. Furthermore, 34.9% and 5.56% of the participants were demonstrated to have anemia and malnutrition, respectively. Nutrition status was positively associated with hemoglobin levels (r = 0.241, p = 0.007) and negatively related to SARC-F scores (r = −0.190, p = 0.034). Older people with anemia show an increased risk of malnutrition at an odds ratio (OR) of 3.375. Moreover, individuals with anemia were at a higher risk of developing sarcopenia (OR 4.982) than those with no anemia. However, individuals with a high level of inflammatory markers, e.g., a high systemic inflammatory response index (SIRI) and monocyte-to-lymphocyte ratio (MLR), had a higher risk of sarcopenia than those with low SIRI and MLR values. The systemic immune–inflammation index (SII) and platelet-to-lymphocyte ratio (PLR) were also positively associated with SARC-F scores. Conclusions: The association between sarcopenia, malnutrition status, and anemia might overlap in clinical manifestation. In addition, future research directions regarding the utility of routine CBC testing should focus on sarcopenia and malnutrition status.